Tracing the Equity on Islamic Heirs: The Reach of Inheritance of Substitute Heirs on the Compilation of Islamic Law - Muhammad Fajri; Oyo Sunaryo Mukhlas; Atang Abdul Hakim (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2023)
The institutionalization of substitute heirs in Islamic inheritance law in Indonesia is a breakthrough based on the principles of justice and humanity for heirs who are left behind, but this regulation is considered vague, has multiple interpretations, and can even disrupt the basic principles of Islamic inheritance. The existence of regulations on substitute heirs is very influential in the distribution of inherited assets, as parties who were not entitled to inheritance become entitled to it. This is a normative study with statutory, conceptual, and political approaches. The results of the study indicate that the policy of forming a substitute heir law in terms of updating and developing Islamic inheritance law in Indonesia is inseparable from the situation and condition of legal requirements, which are more or less influenced by the values that live in society and the continuous developments in society itself, especially in aspects of justice. However, the regulation needs to be revised or corrected in the content of the article so that it is right on target and does not have multiple interpretations within its reach, so that it is in line with the objectives of the law, namely justice, benefit, and legal certainty.